Hegemonic Masculinity and Homosexuality in Contemporary Indonesian Motion Picture - Tarihoran, Rezky Khoirina; Wardana, Muhammad Kiki (International Journal Linguistics of Sumatra and Malay, 2023)
Homosexuality in Indonesia is examined in through its contemporary motion picture. The data for this study came from the motion picture named Arisan! released in 2003. This study incorporated Foucault's theory of sexuality as a social construction, Connell's Hegemonic Masculinity, and A,J Greimas’ Narrative Structuralism . Numerous findings can be found in the research, including the actantial model and functional model of the story in Arisan!. Additionally, this research discovered that homosexuality in Indonesia is subordinated.